The Neural Impact of a Brief Mindfulness and Improvisational Singing Practice on Music Performance Anxiety - Angela Boland; Kayla Boileau; Nicola Oddy; Laurie-Ann Welch; Nicole Stanson; Gilles Comeau; Andra Smith (Voices)
Music Performance Anxiety (MPA) negatively impacts musicians’ personal lives, professional functioning, and performance quality, and is most prevalent in young adulthood. This mixed methods study investigated whether two weeks of a novel intervention called Environmental Vocal Exploration (EVE; Oddy, 2022), combining mindfulness and vocal improvisation, could alter neural activity associated with MPA in young musicians. The EVE intervention was compared with 1) a traditional two-week mindfulness program and 2) no intervention. Pre- and post-intervention, 27 musicians aged 18–28 (n = 7: EVE, n = 10: mindfulness, n = 10: no intervention) completed an anxietyprovoking task and a letter N-back working memory task during fMRI. A thematic analysis was also conducted on discussion transcripts from EVE sessions. During the anxietyprovoking task, blood flow in emotional processing and attention-related brain areas (e.g., limbic and salience network areas) increased from pre- to post-EVE, consistent with themes (e.g., present-moment awareness). During the post-intervention N-back, EVE participants showed less activity than the other groups in cognitive processing areas (e.g., middle cingulate gyrus), indicating enhanced neural efficiency. Both interventions may impact neural activation linked to MPA, through increased attentional and emotional regulation. Vocal improvisation in a mindfulness intervention seemed to augment such effects. Results support further study of EVE’s use for MPA.